Possible link between global warming and rainfall trends in the Mekong Basin. [Abstract only]. - Lacombe, Guillaume; Smakhtin, Vladimir U.; Hoanh, Chu Thai (2013)
Assessing the impacts of global warming on rainfall is crucial in the Mekong region where food production mostly relies on rainfed agriculture. Changes in rainfall in recent decades, and their possible associations to climate change, remain poorly understood in Southeast Asia. Spatial and temporal rainfall variability, observed at various scales, often explain the apparent inconsistencies between previous rainfall trend analyses. To address these problems, we used a trend detection test able to discriminate multiyear variability and long-term unidirectional trends in rainfall time series. Regional testing enabled the detection of significant synoptic disturbances that remain insignificant at the local level because of the high variability of small-scale rainfall events. Regional and local trends in rainfall intensity, frequency, seasonality, and extremes were analysed in the central Mekong Basin over the period 1953-2004. Our results indicate that dry season rainfall has significantly increased in frequency (more rainy days) and intensity (higher cumulative rainfall depths). A significant positive trend was also observed in the annual number of rainy days. Although statistically insignificant, wet season rainfall followed the same pattern of change. These regional changes were found to be consistent with rainfall alterations already observed in the neighbouring south-eastern part of China and attributed to the weakening of the East Asia Summer and Winter Monsoons. Consistency in rainfall changes observed in Continental Southeast Asia and in South-Eastern China, suggests that these two neighbouring regions have been subject to the same alterations in large-scale atmospheric circulation previously attributed to global warming. These observations suggest that human-induced climate change has started to alter rainfall patterns in the Mekong Basin, confirming the need to account for a non-stationary climate when assessing the water resource availability in this region.